Does the Lord Speak with a Forked Tongue? Solutions for Unity in a Diverse Biblical Corpus - Fitzroy, Peter (Lumen et Vita, 2014)
Does the Bible present a unified message from God to humanity? This paper is an attempt to undertake the task set forth by biblical scholar G. Ernest Wright, who said: “The question of the unity of the Bible’s message is one that will never be satisfactorily solved, though it is one which every generation of Christians must seek to solve.” This investigation, while framed as a “personal attempt,” looks at the biblical-theological issue of unity and diversity within the Bible to try to form some theologically synthetic answer to the above question. This investigation dialogues with the history of biblical interpretation by first looking at issues related to diversity in the New Testament (“Micro-diversity”) and then to the Bible as a whole (“Macrodiversity”) to see if we can understand a “whole Bible biblical Theology.” Finally, this paper explores some of the implications of the answers to these questions for the modern Christians.